2019
DOI: 10.3390/en12101879
|View full text |Cite
|
Sign up to set email alerts
|

Does Energy-Growth and Environment Quality Matter for Agriculture Sector in Pakistan or not? An Application of Cointegration Approach

Abstract: The main objective of this paper is to examine the long-term effects of financial development, economic growth, energy consumption (electricity consumption in the agriculture sector), foreign direct investment (FDI), and population on the environmental quality in Pakistan during the period of 1980 to 2016. We use CO2 emissions from the agriculture sector as a proxy indicator for environmental quality. We employ various unit root tests (e.g., ADF, PP, ERS, KPSS) and structural break unit root tests (Z&A, CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…Consequently, the non-renewable energy consumption roots are a more indispensable input for industrial and economic progress compared with renewable energy utilization sources. The results of this work are consistent with previous findings in the literature [24,26,[41][42][43][44][45][46][47].…”
Section: Long-run and Short-run Analysissupporting
confidence: 93%
“…Consequently, the non-renewable energy consumption roots are a more indispensable input for industrial and economic progress compared with renewable energy utilization sources. The results of this work are consistent with previous findings in the literature [24,26,[41][42][43][44][45][46][47].…”
Section: Long-run and Short-run Analysissupporting
confidence: 93%
“…The findings of the study showed a stronger impact of the variables on the GDP per capita in the long run than that of in the short run. Similar to the Chandio et al's findings, the researchers suggested that the government should promote the use of renewable energy resources and make proper decision on reducing the CO 2 emissions [28]. One of the controversial debates in environmental economics, which began in the 1980s, is the relationship between environmental pollution and economic growth.…”
Section: The Economic Growth Energy and Co 2 Emissions Nexusmentioning
confidence: 54%
“…Chandio, et al [28] conducted a research to examine the long run relationship between the financial development, economic growth, energy consumption in the form of electricity consumption in the agriculture sector, foreign direct investment, and population on the quality of environment in Pakistan during 1980-2016.…”
Section: The Economic Growth Energy Trade Population Financial Dementioning
confidence: 99%
See 2 more Smart Citations